1999
DOI: 10.1002/hep.510300135
|View full text |Cite
|
Sign up to set email alerts
|

Complex feedback regulation of bile acid synthesis in the hamster: The role of newly synthesized cholesterol

Abstract: Hepatic bile acid synthesis is regulated by recirculating bile acids, possibly by modulating the availability of newly synthesized and preformed cholesterol. Because data in the hamster on this mechanism are lacking, we fitted these animals with an extracorporeal bile duct and administered tritiated water intraperitoneally to label newly formed cholesterol. After interruption of the enterohepatic circulation, physiological and double-physiological doses of conjugated cholate (25 or 50 mol/100 g · h) or of unco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 65 publications
1
17
0
Order By: Relevance
“…Therefore, HDL is crucial to reverse cholesterol transport (48), whereby newly synthesized cholesterol is transferred from peripheral tissues to the liver for biliary secretion. Furthermore, we found that the contribution of de novo cholesterol synthesis to biliary cholesterol secretion is z15%, consistent with previous studies (16,(42)(43)(44)(45). Under high dietary cholesterol Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, HDL is crucial to reverse cholesterol transport (48), whereby newly synthesized cholesterol is transferred from peripheral tissues to the liver for biliary secretion. Furthermore, we found that the contribution of de novo cholesterol synthesis to biliary cholesterol secretion is z15%, consistent with previous studies (16,(42)(43)(44)(45). Under high dietary cholesterol Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Biliary cholesterol secretion derives from either dietary or newly synthesized cholesterol or both (42)(43)(44)(45). Obviously, in an animal receiving no dietary cholesterol, all biliary cholesterol must ultimately be derived from de novo synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…1,8,9 Because only a small fraction (5%-20%) of biliary cholesterol may be derived from de novo synthesis, [10][11][12] the bulk must be supplied by lipoproteins. Emerging evidence suggests that HDL plays a role for biliary cholesterol secretion, not only in small rodents (e.g., mice) carrying plasma cholesterol mainly in HDL, but also in humans where most of the cholesterol is transported in LDL.…”
mentioning
confidence: 99%
“…In contrast to studies by Hellerstein and Neese 39 and our own previous work, 9 [1][2][3][4][5][6][7][8][9][10][11][12][13] C]acetate was infused intraduodenally and not intravenously. Because of the preferential hepatic clearance of acetate from portal blood, 35,40 the dose could be reduced to one third of the amount given intravenously, and both experimental procedures resulted in comparable cytosolic [ 13 C]acetate enrichments.…”
Section: Discussionmentioning
confidence: 99%
“…In rats and hamsters the amount of newly synthesized cholesterol secreted into bile amounts to 8% to 18% and 2% to 5%, respectively. [3][4][5][6] In humans, most of the indirect evidence using standard radioisotope kinetics supported that 20% of biliary cholesterol were derived from de novo synthesis, 7 the majority being preformed cholesterol supplied by high-density lipoprotein cholesterol. 8 We have recently shown that the mass isotopomer distribution analysis (MIDA) technique allows for the direct measurement of the 4% to 5% of newly synthesized cholesterol formed from [ 13 C]acetate in bile and also that a significantly higher proportion of de novo cholesterol is secreted into bile as opposed to plasma in healthy individuals' circulation.…”
mentioning
confidence: 99%